In vivo reflectance confocal microscopy features of a large cell acanthoma: report of a case - Neda Shahriari; Jane Margaret Grant-Kels; Harold S. Rabinovitz; Margaret Olivieri; Alon Scope (Mattioli1885, 2016)
Reflectance confocal microscopy (RCM) is an FDA approved noninvasive optical imaging technique that acquires cellular level-resolution skin images in vivo. Herein, we report a case of histopathologically proven large cell acanthoma (LCA) whose RCM features simulate those of squamous cell carcinoma in situ.